Pengaruh Motivasi, Inovasi dan Efikasi Diri Terhadap Minat Berwirausaha Mahasiswa D III Perhotelan Politeknik Harapan Bersama Tegal - Wiyanti Wiyanti; Tantri Adithia Sabrina (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2024)
Growing entrepreneurial interest cannot be done immediately without the encouragement that can drive a person's entrepreneurial spirit. The growth of student interest in entrepreneurship is influenced by motivation. Growing interest in entrepreneurship also requires the role of innovation as a response to the demands and needs of a person to survive in the midst of competition. Student entrepreneurial interest can be seen from the characteristics of an entrepreneur, namely student confidence in entrepreneurship, interest, and courage to take risks when they are entrepreneurs in the future and future-oriented when they are entrepreneurs. A person's confidence in their ability to complete a job (self-efficacy) will affect interest in entrepreneurship because a person's motivational condition is based more on what they believe than what is objectively true. This study aims to determine the effect of motivation, innovation and self-efficacy on entrepreneurial interest of D III Hospitality students at Harapan Bersama Polytechnic Tegal. This research is quantitative research with a survey approach. The analysis used is multiple linear regression analysis with instrument test using validity test and reliability test. The expected target of this study is to determine the significant influence of motivation, innovation and self-efficacy on entrepreneurial interest of D III Hospitality Polytechnic students of Harapan Bersama Tegal.The results of the study prove that there is a positive influence of motivation, innovation, self-efficacy on entrepreneurial interest in D III Hospitality students of Harapan Bersama Polytechnic Tegal. The higher the motivation, innovation, self-efficacy, the interest in entrepreneurship in D III Hospitality students of Harapan Bersama Polytechnic Tegal will also increase.